(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this study is to look into the function of human resource management in the well-being of Mizoram University’s central library employees. Employee well-being issues at work, such as recruiting, remuneration, work distribution, training, development, and security, were explored in the study. Well-structured questionnaires were distributed to library staff for the study, and they all returned them. The study’s findings demonstrate that library employees’ well-being must be prioritized, with changes and improvements made as needed, because a satisfied employee produces higher productivity.